Teaching with the screen : pedagogy, agency, and media culture - Leopard, Dan, 1959- (Routledge, 2013)
"Teaching with the Screen explores the forms that pedagogy takes as teachers and students engage with the screens of popular culture. By necessity, these forms of instruction challenge traditional notions of what constitutes education. Spotlighting the visual, spatial, and relational aspects of media-based pedagogy using a broad range of critical methodologies, textual analysis, interviews, and participant observation and placing it at the intersection of education, anthropology, and cultural studies, this book traces a path across historically specific instances of media that function as pedagogy: Hollywood films that feature teachers as protagonists, a public television course on French language and culture, a daily television "news" program created by high school students, and a virtual reality training simulation funded by the US Army. These case studies focus on teachers as pedagogical agents (teacher plus screen) who unite the two figures that have polarized earlier debates regarding the use of media and technology in educational settings: the beloved teacher and the teaching machine"--